UMRAH HEALTH SURVEILLANCE SYSTEM IN PORT HEALTH OFFICE CLASS I SURABAYA - Bangun Cahyo Utomo; Chatarina Umbul Wahjuni; Windhu Purnomo (Universitas Airlangga, 2019)
Background: The number of Umrah pilgrims is three times higher than hajj pilgrims. The Hajj pilgrims’ welfare can be monitored through an established surveillance system, while Umrah pilgrims’ welfare hasn’t had a surveillance system. Purpose: This study aims to develop an Umrah pilgrims’ health surveillance system in the Port Health Office (PHO)Class I of Surabaya. Method: This research was a descriptive study conducted at Port Health Office Class I of Surabaya in February-August 2018. The data was collected by in-depth interviews. The informants were the officers of Surabaya Port Health Office Class I, the Hajj Guidance Group (KBIH), and the operational manager of Umrah airline. The research variables were data collection, analysis, reports, reports of extraordinary conditions, dissemination, and utilization of results at the Port Health Office (PHO) Class I of Surabaya Results: The general objective of Umrah pilgrims’ health surveillance system is the availability of epidemiological information on Umrah pilgrims’. The data collection was conducted actively and passively on the departure, in Saudi Arabia, and on arrival. The data analysis and interpretation aim to determine the frequency, distribution or proportion of Umrah pilgrims based on demographics, disease history, vaccination status and suspected findings. The information obtained was disseminated to the internal party of PHO Class I of Surabaya, stakeholders across sectors or programs and communities. System evaluation uses the attribute approach and takes place once a year. Conclusion: The system is developed based on the components of data collection, data processing, data analysis and interpretation, and dissemination